Heavy Metals in Sediments of Subarctic Meromictic Lakes of the White Sea as Possible Tracers of Environmental Changes - Dmitry F. Budko; Liudmila L. Demina; Elena D. Krasnova; Dina P. Starodymova (Journal of Marine Science and Engineering, 2023)
Meromictic lakes of the marine coast, quite widely distributed in the northern hemisphere, are the result of climate changes and glacier retreat. The bottom sediments of these lakes serve as a geological chronicle of the history of marine basin’s development with the geochemical occurrence forms of elements indicate various processes of their accumulation. This paper presents research results concerning the occurrence of forms of heavy metals in lake sediments along the coast of the White Sea. These results are based on a sequential seven step leaching procedure, followed by ICP-MS analysis and subsequent statistical data processing. To determine differences among the examined geochemical parameters, Pearson’s correlation analysis and Ward’s cluster analysis were utilized. The total content of Cr, Mn, Fe, Co, Ni, Zn, V, and Pb in the sediments did not exhibit significant differences based on their degree of isolation from the sea. The major contribution to deposition of these metals in sediments of the meromictic lakes studied is the residual form, encompassing the mineral matrix of the sediment. At the same time, the elevation of mobile forms for all the metals examined corresponds to an increase in the isolation of lakes from the White Sea. In the meromictic lake sediments, concentrations of Cu, Mo, and U demonstrated significant increases in forms tightly bound to organic matter, while Cd exhibited an association with Fe-Mn oxyhydroxides. Notably, a significant difference in the occurrence forms of Cu, Cd, Mo, and U was evident in the reduced sediments of meromictic lakes when compared to those of open sea bays. The meromictic lakes along the White Sea coast, positioned at various stages of isolation, hold promise for investigating the migration of metals in response to environmental changes.